Function design for fault analysis in transmission lines to be executed in a digital fault recorder (2017)
"This document presents the work developed as graduation project in electrical engineering by Alexei Rodriguez. It deals with the study of mathematical methods for fault analysis in transmission lines. The main goal is to choose, implement and test a fault location method with an error under 2%. Additionally, the Clarke transformation is studied as an alternative for a quick response fault detection method, the Fourier transform with a moving window is used as a method for calculating the phasorial state of current and voltage signals and their change throughout time and through this signals calculate fault trajectory and represent it in an RX plane." -- Tomado del Formato de Documento de Grado.